ตัวประกอบการกระแทกตามตำแหน่งต่างๆ บนพื้นสะพานจากข้อมูลการทดสอบภาคสนาม - เอกวิทย์ ขันแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This research studies the impact factor at different locations on a bridge slab from monitoring of actual bridge responses under normal traffic condition. The main objective is to compare the impact factors at mid-span with other bridge locations because, for convenience, the existing research studies as well as relevant design standards treat the impact factor as a constant value throughout the bridge length. The impact factors were commonly considered only at bridge’s mid-span assuming the value is higher than other locations. However, this assumption might be incorrect and possibly leads to an unsafe bridge design. Therefore, this research studies the impact factors at different locations on bridge slabs from field test data. The bridge strain histories are measured at L/3, L/2 and 2L/3. Then the corresponding bridge moments at those sections can be obtained. The bridge is pre-stressed concrete slab with a simply supported span having length of 10 meters. The bridge responses under normal traffic condition are monitored. The impact factors induced by the passing 10-wheel trucks are of interest. Similar to the analytical study, the measured results show that the impact factors at other locations can significantly higher than those obtained at bridge’s mid-span. In addition, the obtained values indicate the possibility of having the values higher than that specified in the design standards. This may lead to the under-design of the bridge deck. Therefore, the modification or improvement of the bridge’s impact factor should be addressed.